2020
DOI: 10.31616/asj.2019.0332
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Early Disc Height Loss Following Lateral Lumbar Interbody Fusion

Abstract: To analyze the factors influencing early disc height loss following lateral lumbar interbody fusion (LLIF). Overview of Literature: Postoperative disc height loss can occur naturally as a result of mechanical loading. This phenomenon is enabled by the yielding of the polyaxial screw heads and settling of the cage to the endplates. When coupled with cage subsidence, there can be significant reduction in the foraminal space which ultimately compromises the indirect decompression achieved by LLIF. Methods: Sevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Kaliya-Perumal et al reported that over-corrected postoperative disc height was correlated with subsequent disc height loss during early follow-up. 19 Accordingly, the study of subsidence following standalone anterior cervical discectomy and fusion cage by Igarashi et al also reported a higher risk of cage subsidence when using greater cage height. 20 Thus, we strongly recommend an optimal cage height of less than 12 mm to avoid excessive mechanical stress on the vertebral endplate.…”
Section: Discussionmentioning
confidence: 99%
“…Kaliya-Perumal et al reported that over-corrected postoperative disc height was correlated with subsequent disc height loss during early follow-up. 19 Accordingly, the study of subsidence following standalone anterior cervical discectomy and fusion cage by Igarashi et al also reported a higher risk of cage subsidence when using greater cage height. 20 Thus, we strongly recommend an optimal cage height of less than 12 mm to avoid excessive mechanical stress on the vertebral endplate.…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative DH, FH, SA, and LL values in the 11-mm cage height group were smaller than those in the 13-mm cage height group; however, the group had similar DH, FH, and SA but not LL immediately postoperatively and at 12 months later, demonstrating the strong lumbar alignment restoration of the cage and the importance of its proper cage height in the LLIF procedure. Previous study demonstrated that optimal cage height in LLIF was important because the postoperative increase in disc height and the disc height loss at the final follow-up were closely associated [24]. Barone et al [9] demonstrated that disc angle and lumbar lordosis restorations were effective because lordotic cages were utilized in the LLIF, with the improvement magnitude significantly higher in the lower cage height group for DH, FH, SA, and LL immediately postoperatively and at final follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the surgeon may consider placing a larger cage in a narrow disc space for indirect decompression at LLIF. It has also been reported that the greater the postoperative increase in DH by LLIF, the greater the DH loss throughout early follow-up [ 32 ]. This means that greater cage height has been shown to increase the risk of cage subsidence.…”
Section: Discussionmentioning
confidence: 99%